Perencanaan Wisata Air Terjun Aek Martua Dengan Konsep Media Digital - Dodi Sukma RA; Roki Hardianto; Ardiya Ardiya (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2022)
Arboretum is a Rokan Hulu Regency, there are various kinds of attractions, which consist of cultural tourism, culinary tourism, historical tourism, religious tourism and nature tourism. The natural tourism object in Rokan Hulu Regency is Aek Martua Waterfall. This waterfall has a height ranging from 15 meters to the highest reaching 40 meters. The uniqueness and privilege, makes many tourists call the Aek Martua Waterfall as the Thousand Stairs Waterfall. That is what creates a tourist attraction so that tourists visit there. The purpose of this study is to identify the potential and attraction of Aek Martua's water. Potential measurement using the One Score-One Indicator System Method, namely giving a score of 1 (one), for 1 (one) indicator, with the scale used is 1-7 (a development of the Likert scale 1-5). The use of scale 1-7 is applied because it is in accordance with the character of Indonesian society which articulates a value in great detail (Avenzora 2008). Value score 1-7. Potential Assessment and Tourism Attraction consisting of; (1) Uniqueness (2) Beauty (3) Scarcity (4) Timeliness (5) Accessibility (6) Sensitivity (7) Social Function with the average Potential and Attractiveness value of Aek Martua Waterfall (5.11), i.e. attractive, so what needs to be added are facilities and infrastructure as well as one-stop tour management.